Analisis Pengaruh Brand Awareness, Label Halal dan Religiusitas Terhadap Keputusan Pembelian Produk Kosmetik Halal - Mohammad Rosyada (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Based on the consumption theory in Islam, moslems are not permissive consumers. All things regarding consumption are guided by Islamic law, where consumers are obliged to consume something that is halal and thayyib. Wardah is a halal cosmetic product which is a pioneer of halal cosmetic products in Indonesia. This research aims to determine the effect of Brand Awareness, Halal Label and Religiosity on the Purchase Decision of Halal Cosmetic Products (Study of Wardah Cosmetics Customers, Pekalongan City). This research is a quantitative research whose data source is primary data from Wardah cosmetic product customers in Pekalongan City. Samples were taken using the Accidental Sampling method with a sample size of 97 people and multiple linear regression was used as the method of analysis. The results of this research indicate that Brand Awareness partially has a significant effect on the Purchase Decision of Wardah cosmetics in Pekalongan City, but Halal Label and Religiosity partially have no significant effect on Wardah cosmetic purchasing decisions in Pekalongan City. Meanwhile, simultaneously Brand Awareness, Halal Label and Religiosity affect the Purchase Decision of Wardah cosmetics in Pekalongan City. The Adjusted R Square value of 0.106 indicates that the 10.6% increase in Wardah cosmetic purchasing decisions in Pekalongan City (Y) can be explained by independent variables, namely Brand Awareness, Halal Labels and Religiosity. While the remaining 89.4% is explained by other variables not examined in this research.